Misunderstandings about the effect of legalizing abortion - Faundes, Anibal (2015)
Abortion laws are generally liberal in most of the developed countries and restrictive in developing countries, particularly in Latin America, with two exceptions. International health and human rights organizations promote broader access to safe abortion based on its effectiveness in immediate reduction of maternal morbidity and mortality. Laws remain restrictive in Latin America because of the erroneous concept that liberalization of the law would increase the number of induced abortions, something most people would not like. This is a crucial misunderstanding because evidence shows abortions are not less in countries with restrictive laws and number of abortions does not increase following liberalization of the law. It is also believed that most people are against liberalization of the law, but further inquiry reveals that most people are against punishing women who have abortions. The main misunderstanding is the belief that there are people “in favor of abortion”, while even women who abort do not like abortion. The real difference is that there are people who believe that keeping restrictive laws can prevent abortion and others accept evidence which shows that increasing access to safe abortion not only reduces suffering and deaths but contributes to reduce induced abortions.